Upaya PDI Perjuangan dalam Mencapai Kuota 30% Keterwakilan Perempuan di DPR RI pada Pemilihan Umum 2024 - Hia, Emilina Fransiska (Brawijaya University, 2025)
This study examines the limited representation of women from the Indonesian Democratic Party of Struggle (PDI Perjuangan) in the 2024 general election. As the party with the highest vote share and female leadership, PDI Perjuangan achieved only 24.5% female representation in the national parliament (DPR RI), falling short of the 30% quota mandated by Law No. 7 of 2017. This study aims to analyse the efforts and challenges the party faces in fulfilling the quota. A qualitative approach was used with a single case study design. Data were collected through in-depth interviews, limited observation, document analysis, and literature review and analysed using Miles and Huberman’s interactive model. The findings indicate that the party has attempted to implement a feminising politics strategy, including rhetorical, promotional, and guarantee-based dimensions. However, its implementation remains suboptimal. Obstacles to rhetorical equality stem from the disconnection between discourse and institutional action. In terms of promotion, political education and cadre training have not been systematically linked to the nomination process. Regarding guarantees, internal quota policies are not supported by strategic placement mechanisms or sufficient logistical support. These findings suggest that the party's affirmative strategies have not been consistently and comprehensively institutionalised. This study concludes that weak implementation across the three strategic dimensions contributed to PDI Perjuangan’s failure to meet the women’s representation quota in the 2024 election